EDITORIAL: Hair Splitting at What Cost? - Haque, Anwar Ul (International Journal of Pathology, 2022)
No doubt, Immune stains and genetic marker tests have brought new insight in pathology diagnoses and have contributed toward better diagnosis and management. They have helped us in tracing the tissue origin of the tumors. As it is said aid that too much of everything is bad, too much hair splitting may not that be good or beneficial! At times, immune stains and genetic markers may be very expensive. Most developing countries invariably follow developed countries almost blindly, so their health providers recommend such tests and strategies for almost every malignancy. In developing countries where most people have hard time to meet ends, can they bear the cost of these expensive tests? The cost consideration must be evaluated in relation to personal income and affordability. In addition to the cost there are many other concerns that also need to be addressed; not only for developing countries but also for the developed world.